The Effect of Digital Content Marketing and Customer Experience on Brand Loyalty of Nuju Coffee in Bandar Lampung - Oktavia, Friskila; Yusendra, M. Ariza Eka (Proceeding International Conference on Information Technology and Business, 2023)
This study aims to determine whether digital content marketing and customer experience have a significant influence or not on the development of brand loyalty from Nuju Coffee cafe. The results of this study are expected to be a reference for companies whether to continue or change the strategies that have been implemented to be able to win competition in the increasingly fierce cafe market. This type of research is causality explanatory quantitative research, with the population being followers of the @nujucoffe Instagram account of 32,300 followers and the sample to be studied as many as 100 respondents. The analytical tool used is Multiple regression analysis to determine whether there is a positive causal relationship between Digital Content Marketing and Customer Experience on Brand Loyalty from Nuju Coffee Bandar Lampung.Â Keywords-digital marketing, brand loyalty, digital content marketing, instagram, customer experience